The bear and the dragon - Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 2000)
Being President, Jack Ryan discovers, doesn't get any easier, particularly not when domestic pitfalls await him at every turn and in Moscow someone may have tried to take out the chairman of the SVR (formerly the KGB) with a rocket-propelled grenade. Who were the potential assassins - were they Russian mafia, disaffected former KGB or something far more dangerous? Even while Ryan dispatches his most trusted eyes and ears to find out the truth, forces in China are moving ahead with a plan of audacious proportions. If they succeed, the world will never look the same. If they fail... the consequences will be unspeakable.